Performance analysis of a cross-axis wind turbine from wind tunnel experiments - Wang, Wei Cheng; Chong, Wen Tong; Chao, Tien Hsin (Elsevier, 2018)
Wind energy has been considered as one of the primary renewable energy sources globally. In urban areas, due to the irregular arrangement of buildings, small scale wind turbine plays an important roles for household energy grid. In this study, a newly designed small scale wind turbine namely cross-axis wind turbine (CAWT), which combines the characteristics of horizontal and vertical axis wind turbines (HAWT and VAWT), was examined experimentally on the power performance in a low speed, open-loop circuit wind tunnel at Reynolds numbers of Re = 42900, 57100 and 71400. The results were compared to a traditional straight-bladed VAWT. The performance analyses are evaluated in terms of static performance, dynamic performance, and blade force measurement. The results of static and dynamic performances indicate that CAWT has not only better self-starting characteristics but also higher power coefficients over VAWT. The tangential forces measurement on the horizontal blade of CAWT proves its superior power performance compared to VAWT.